A profile of delafloxacin in the treatment of adults with community-acquired bacterial pneumonia. Issue 6 (3rd June 2022) - Gómez-Zorrilla, Silvia; Sendra, Elena; Horcajada, Juan P.
ABSTRACT: Introduction: Community-acquired bacterial pneumonia (CABP) is the most common infectious cause of hospital admission in adults, and poses a significant clinical and economic burden. At the same time, antimicrobial resistance is increasing worldwide with only a few new antibiotics developed in recent years. Delafloxacin is an anionic fluoroquinolone available in intravenous and oral formulations and with a broad spectrum of activity targeting Gram-positives, including methicillin-resistant Staphylococcus aureus (MRSA), gram-negative organisms, and atypical and anaerobic organisms. It also has a better adverse event profile compared to other fluoroquinolones. Areas covered: This article reviews the current epidemiology of CABP, etiologic agents and current resistance rates, current treatment guidelines, characteristics of delafloxacin (chemistry, microbiology, PK/PD), clinical efficacy and safety in pneumonia and other indications, and regulatory affairs. Expert opinion: Delafloxacin's susceptibility profile against respiratory pathogens, bioequivalent intravenous and oral formulations and favorable safety profile, support its use for the treatment of CABP. It could be useful as empirical treatment in countries with high rates of penicillin-resistant S. pneumoniae and in patients with suspected or documented pneumonia due to MRSA. In post-influenza staphylococcal bacterial pneumonia, MRSA could be also considered an important pathogen.